Microencapsulation of Olive Oil: A Comprehensive Review - Chaabane, Donia; Yakdhane, Asma; Vatai, Gyula; Koris, András; Nath, Arijit (Periodica polytechnica. Chemical engineering., 2022)
Olive oil has been received a great importance around the globe because it provides unique functional value. Olive oil prevents the risks of several chronic and acute metabolic disorders because it is enriched with monounsaturated fatty acids, antioxidant phenolic compounds, vitamin E and vitamin K. Unfortunately, oxidative deterioration of fatty acids in olive oil provides short shelf life and reduces biological activities. It is responsible for undesirable organoleptic properties. It may belief that one of the solutions to preserve the quality of olive oil is microencapsulation. In this review, comprehensive information about techniques to prepare olive oil microcapsule is represented. To prepare olive oil microcapsule, emulsification of olive oil with different wall materials (matrixes) has been adopted as a primary step. Subsequently, dehydration of emulsion by spray drying or freeze drying or coacervation process has been adopted to prepare olive oil microcapsule. Moreover, microcapsule of olive oil has been prepared by extrusion technology. Biopolymers, such as proteins and polysaccharides have been used as wall material for encapsulation of olive oil. As stable emulsification is one of important issue to produce microcapsule, several emulsifiers, such as lecithin, tween 20 have been used during emulsion preparation. Different characteristics of the microcapsule of olive oil are summarized because it is influenced by several factors during preparation of microcapsule. In later exercise, several applications of encapsulated olive oil in food, pharmaceutical and cosmetic industries are represented in comprehensive way. It may expect that this review article will receive attention in industries and academic sectors.